Reflection of Celestial Luminaries, Constellations, andthe Structure of the Universe in the Archaeological Artifacts of Ancient Armenia - Simonyan, H. E.
Numerous evidences of observing the starry sky since ancient times have been recorded in the Armenian Highlands, which have been imprinted in the form of geometric images on rocks, stone carvings, and archaeological artifacts. The oldest cosmogonic myths have been preserved in folklore, mythological narratives, epics, ethnographic rituals, and charms. This article is devoted to the interpretations of the myths that have reached us about the universe, constellations, the Sun, stars, comets, meteors and other celestial bodies, and the ancient and medieval geometric signs that reproduce them.
Keywords: Astrophysics